2019
DOI: 10.26858/talenta.v4i2.7618
|View full text |Cite
|
Sign up to set email alerts
|

Peran Kegigihan Dalam Hubungan Growth Mindset Dan School Well-Being Siswa Sekolah Menengah

Abstract: This study investigates the relationship between school well-being, growth mindset, and grit. The subjects involved in this study are students from grade 12 in high public and private schools in Purbalingga, Central Java (n=418). The research method used is quantitative method with data collection through three questionnaires, i.e., School Well-Being Scale (32 items, α=0.853); Mindset Scale (20 items, α=0.804); and Grit Scale for Children and Adult (12 items, α=0.774). Results indicated a positive affact growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 19 publications
(32 reference statements)
1
13
0
3
Order By: Relevance
“…Concerning adolescents, some study results found that grit can be associated with well-being (Datu, 2016;Disabato, 2016;J. Schmidt, 2017;Wahidah & Royanto, 2019). With well-being, it is expected to be a useful thing that helps teenagers face their crucial times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning adolescents, some study results found that grit can be associated with well-being (Datu, 2016;Disabato, 2016;J. Schmidt, 2017;Wahidah & Royanto, 2019). With well-being, it is expected to be a useful thing that helps teenagers face their crucial times.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, the study of grit began to be widely conducted in the field of education, both to lecturers (Arifin & Puteri, 2019), college students (Chrisantiana & Sembiring, 2017;Izaach, 2017;Purba & Djaling, 2019;Sudarji & Juniarti, 2020;Vivekananda, 2018), and high school students (Anindita, 2019;Arpinda, 2019;Hirani, 2019;Kristianto, 2017;Rosalina, 2016;Wahidah & Royanto, 2019;Yobel, 2018). Nevertheless, the findings of the study on grit still need to be developed to enrich the literature and discussion, especially the great benefits for students.…”
Section: Introductionmentioning
confidence: 99%
“…Discussions about school well-being were investigated in several settings, including at, among others, students of State Vocational Schools (Andriany & Setyawan, 2016), Pharmacy Foundation Vocational School (Nanda & Widodo, 2015), college students (Rizki & Listiara, 2015), middle school students (Abdillah et al, 2020), high school student (Wahidah & Royanto, 2019) (Hongwidjojo et al, 2018) (Evans et al, 2018) (Ramberg et al, 2019), Christian high school students (Imelda, A., & Wahyuningrum, 2017). In this study, it will be focused on the setting of Muhammadiyah Vocational High School Students because vocational secondary education is a secondary education level that prioritizes the development of students' abilities to carry out certain types of work, which is expected after graduates of Muhammadiyah Vocational Schools students have competencies according to the needs of the world of work and have a noble character so that in this study focused on students of SMK Muhammadiyah.…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…On the other hand, the fixed mindset assumes that everything is permanent and difficult to change, including intelligence and morals. The growth mindset has been widely studied to be able to have a positive impact such as school well-being and Grit (Wahidah & Royanto, 2019), achievement (Sawitri, 2019), entrepreneurial behavior on the internet (Dewi et al, 2020), and self-regulated learning (Putri & Royanto, 2021) The mindset possessed by individuals is caused by environmental factors such as parents, family, community, friends, mass media (Iskandar, 2008). In addition, other studies say that there are demographic factors that affect the growth mindset, such as gender.…”
Section: Introductionmentioning
confidence: 99%